Effectiveness of Quinolone Prophylaxis in Pediatric Acute Leukemia and Hematopoietic Stem Cell Transplantation: A Systematic Review and Meta-analysis. (3rd November 2022) - Leardini, Davide; Muratore, Edoardo; Abram, Nicoletta; Baccelli, Francesco; Belotti, Tamara; Prete, Arcangelo; Gori, Davide; Masetti, Riccardo
Abstract: The effectiveness of quinolone prophylaxis in high-risk hematological pediatric patients is controversial. A systematic review was performed according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, including studies that involved children and young adults undergoing chemotherapy for acute leukemia or hematopoietic stem cell transplantation (HSCT) who received quinolone prophylaxis compared with no prophylaxis. A meta-analysis was performed on bloodstream infections and neutropenic fever. Data regarding the impact of prophylaxis on overall survival, antibiotic exposure, antibiotic-related adverse effects, antibiotic resistance, Clostridium difficile infections, fungal infections, length of hospitalization, and costs were reviewed in the descriptive analysis. Sixteen studies were included in the qualitative analysis, and 10 of them met the criteria for quantitative analysis. Quinolone prophylaxis was effective in reducing the rate of bloodstream infections and neutropenic fever in pediatric acute leukemia compared with no prophylaxis, but it had no significant effect in HSCT recipients. Prophylaxis was associated with a higher rate of bacterial resistance to fluoroquinolones and higher antibiotic exposure.